Applications of muon absorption radiography to the fields of archaeology and civil engineering. (10th December 2018) - Saracino, G.; Ambrosino, F.; Bonechi, L.; Cimmino, L.; D'Alessandro, R.; D'Errico, M.; Noli, P.; Scognamiglio, L.; Strolin, P.
Abstract : Muon radiography, also known as muography, is an imaging technique that provides information on the mass density distribution inside large objects. Muons are naturally produced in the interactions of cosmic rays in the Earth's atmosphere. The physical process exploited by muography is the attenuation of the muon flux, that depends on the thickness and density of matter that muons cross in the course of their trajectory. A particle detector with tracking capability allows the measurement of the muons flux as a function of the muon direction. The comparison of the measured muon flux with the expected one gives information on the distribution of the density of matter, in particular, on the presence of cavities. In this article, the measurement performed at Mt. Echia in Naples (Saracino 2017 Sci. Rep. 7, 1181. (doi:10.1038/s41598-017-01277-3 )), will be discussed as a practical example of the possible application of muography in archaeology and civil engineering. This article is part of the Theo Murphy meeting issue 'Cosmic-ray muography'.